HARMONISASI HUKUM ADAT HUKUM PERTAHANAN NASIONAL TERKAIT KEPEMILIKAN TANAH DALAM RANGKA PROYEK STRATEGIS NASIONAL - Rahmad, Agus (Jurnal Hukum dan Keadilan, 2023)
Based on the infrastructure development plan, there are 201 national strategic infrastructure projects, including toll roads, ports, airports, railways, industrial estates, economic zones, housing, dams, irrigation networks, drinking water sector, sanitation, sea wall industry, energy sector, technology industry and education. The research utilizes a normative juridical approach. Land in Indonesia is regulated in the Basic Law on Agriculture which contains customary law, especially the recognition of customary rights as stated in Article 5 of the Basic Law on Agriculture which stipulates that the agrarian law that applies to land, water and space is customary law, as long as it does not conflict with national and state interests based on the basis of national unity, with the socialism of the Indonesian Union and with the provisions in this law and other regulations, everything taking into account factors based on religious law. The normative juridical approach is an approach that is carried out based on the main legal material by examining theories, concepts, legal principles and laws and regulations related to this research. Customary law has an important role in the development of national agricultural law, especially the Basic Agricultural Law (UUPA) which is the basis and guidelines in regulations relating to agricultural practices.